2011
DOI: 10.4103/0019-5413.77132
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Mears procedure for Sprengel’s deformity

Abstract: Background:Sprengel’s shoulder is characterized by scapular maldescent and malposition, causing restriction of shoulder and cervical spine movements. It is associated with a variety of other congenital anomalies. Various surgical procedures have been described to treat this anomaly with no consensus as to the surgical procedure of choice. We report the results of the Mears procedure in the treatment of Sprengel’s shoulder.Materials and Methods:Seven children between the age group of two and six years were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Ten papers [ 2 , 13 , 18 , 34 , 39 , 40 , 43 , 51 , 54 , 56 ] reported neither of them, whereas Khairouni et al [ 50 ] described a personal score that analyzed the position of the scapula based on the vertebral level. The mentioned studies reported the same scores as well in the postoperative assessment, except Bhasker [ 41 ], who did not report the postoperative Rigault classification. Only two papers used patient-reported postoperative scores for clinical and functional assessment, such as the DASH Score [ 58 ], the SST Score [ 16 , 58 ] and the PODCI score [ 16 ], whereas most studies reported only subjective evaluations.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Ten papers [ 2 , 13 , 18 , 34 , 39 , 40 , 43 , 51 , 54 , 56 ] reported neither of them, whereas Khairouni et al [ 50 ] described a personal score that analyzed the position of the scapula based on the vertebral level. The mentioned studies reported the same scores as well in the postoperative assessment, except Bhasker [ 41 ], who did not report the postoperative Rigault classification. Only two papers used patient-reported postoperative scores for clinical and functional assessment, such as the DASH Score [ 58 ], the SST Score [ 16 , 58 ] and the PODCI score [ 16 ], whereas most studies reported only subjective evaluations.…”
Section: Resultsmentioning
confidence: 89%
“…Most studies reported the patients’ sex, except three [ 34 , 43 , 57 ], and the affected side, except eight [ 21 , 23 , 43 , 47 , 50 , 54 , 57 , 59 ]. In the preoperative evaluation, 28 studies classified patients according to the Cavendish clinical scoring system [ 2 , 9 , 14 , 16 , 17 , 19 , 20 , 21 , 23 , 33 , 35 , 36 , 37 , 38 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 52 , 53 , 55 , 58 , 59 , 60 ] and 15 studies [ 14 , 15 , 16 , 17 , 19 , 21 , 32 , 36 , 41 , 45 , 48 , 53 , 57 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations